2015
DOI: 10.5888/pcd12.150147
|View full text |Cite
|
Sign up to set email alerts
|

Rural Food and Physical Activity Assessment Using an Electronic Tablet-Based Application, New York, 2013–2014

Abstract: IntroductionA community’s built environment can influence health behaviors. Rural populations experience significant health disparities, yet built environment studies in these settings are limited. We used an electronic tablet-based community assessment tool to conduct built environment audits in rural settings. The primary objective of this qualitative study was to evaluate the usefulness of the tool in identifying barriers and facilitators to healthy eating and active living. The second objective was to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…This approach previously has been successfully pilot tested in diverse locations in the USA, including in lowincome Latino neighborhoods. [20][21][22][23][24] However, it has never been pilot tested in a lowor middle-income country such as Mexico. Low-and middle-income countries are high priorities for physical activity promotion because of increasing levels of physical inactivity, obesity, and the high burden of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This approach previously has been successfully pilot tested in diverse locations in the USA, including in lowincome Latino neighborhoods. [20][21][22][23][24] However, it has never been pilot tested in a lowor middle-income country such as Mexico. Low-and middle-income countries are high priorities for physical activity promotion because of increasing levels of physical inactivity, obesity, and the high burden of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The target sample size was 30 adults aged 45 years and older (8 to 11 per census tract) to achieve saturation of the neighborhood information provided, as seen in US-based studies. [20][21][22][23][24] In these latter studies, it was found that Bsaturation^in relation to basic neighborhood environment issues being identified could be achieved with approximately 8-10 residents from a neighborhood. We also aimed to include a smaller total sample of 10 adolescents ages 11 to 14 years (4 to 5 adolescents per census tract) to complement the information obtained from the adults.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations